2020
DOI: 10.1002/lary.28491
|View full text |Cite
|
Sign up to set email alerts
|

Flexible versus rigid laryngoscopy: A randomized crossover study comparing patient experience

Abstract: Objectives: To compare flexible distal-chip laryngoscopy (FDL) versus rigid telescopic laryngoscopy (RTL) in regard to examinees' pain level, comfort, satisfaction, and preference, and to evaluate the clinician's assessment of the examinees' experience with both exam types. Study Design: Randomized crossover study. Methods: Twenty-three normal adult subjects were recruited to undergo both FDL and RTL; the initial exam type was randomized. Subjects and clinicians completed corresponding questionnaires after eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A randomized crossover study to compare the patient experience between rigid and flexible laryngoscopy was conducted by Clark et al in adult patients [15]. They also concluded that flexible scopy was associated with more discomfort and pain than rigid laryngoscopy.…”
Section: Advantagesmentioning
confidence: 99%
“…A randomized crossover study to compare the patient experience between rigid and flexible laryngoscopy was conducted by Clark et al in adult patients [15]. They also concluded that flexible scopy was associated with more discomfort and pain than rigid laryngoscopy.…”
Section: Advantagesmentioning
confidence: 99%
“…Although this finding has not been reported for patient satisfaction outcomes, this study combines survey responses from ANA members and those from a tertiary referral center, which may lessen the impact of any biases associated with the aforementioned finding. Finally, to date, there does not exist a validated patient satisfaction measurement instrument or disease-specific measure that incorporates these questions for patients with VS; however, similar questions have been implemented across surgical disciplines to effectively capture the patient experience (31)(32)(33).…”
Section: Limitationsmentioning
confidence: 99%